Answer:
R (t) = 60 - 60 cos (6t)
Explanation:
Given that:
R(t) = acos (bt) + d
at t= 0
R(0) = 0
0 = acos (0) + d
a + d = 0 ----- (1)
After
seconds it reaches a height of 60 cm from the ground.
i.e
![R ( (\pi)/(12)) = 60](https://img.qammunity.org/2021/formulas/mathematics/college/i8j5jw9a1iek3dt56au96kph0pncxhj4pm.png)
![60 = acos ((b \pi)/(12)) +d --- (2)](https://img.qammunity.org/2021/formulas/mathematics/college/m2ibomh8sb52x6rd63eglmbdixcrujhjyp.png)
Recall from the question that:
At t = 0, R(0) = 0 which is the minimum
as such it is only when a is negative can acos (bt ) + d can get to minimum at t= 0
Similarly; 60 × 2 = maximum
R'(t) = -ab sin (bt) =0
bt = k π
here;
k is the integer
making t the subject of the formula, we have:
![t = (k \pi)/(b)](https://img.qammunity.org/2021/formulas/mathematics/college/3tdg8w98gtdvrzrrinxpcps9ksjjg0yqgk.png)
replacing the derived equation of k into R(t) = acos (bt) + d
![= \left \{ {{a+d \ for \ k \ odd} \atop {-a+d \ for k \ even}} \right.](https://img.qammunity.org/2021/formulas/mathematics/college/gpgzw89mr51kp3fzpyzi4zpr0j0jygvlre.png)
Since we known a < 0 (negative)
then d-a will be maximum
d-a = 60 × 2
d-a = 120 ----- (3)
Relating to equation (1) and (3)
a = -60 and d = 60
∴ R(t) = 60 - 60 cos (bt)
Similarly;
For
![R ( (\pi)/(12))](https://img.qammunity.org/2021/formulas/mathematics/college/rfi8geate4g7wl1fkevdrwbrtl7qkrv7a5.png)
![R ( (\pi)/(12)) = 60 -60 \ cos ((\pi b)/(12)) =60](https://img.qammunity.org/2021/formulas/mathematics/college/h5md6gi9ahh28ptxguhcy0ojcnmtdnn3ru.png)
where ;
![cos ((\pi b)/(12)) =0](https://img.qammunity.org/2021/formulas/mathematics/college/x1lnhofbxfjdj0n6gpqdo2e8zmou95niye.png)
Then b = 6
∴
R (t) = 60 - 60 cos (6t)